Analisis Blending Bauksit Menggunakan Metode Simplek Di PT. Bumi Khatulistiwa Bauksit Kecamatan Meliau Kabupaten Sanggau, Kalimantan Barat. - Mangunsong, Vico Malo; Syafrianto, Muhammad Khalid; Aprilia, Ricka (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
PT conducted the blending calculations. Bumi Khatulistiwa Bauksit has not yet yielded efficient results. In terms of grade, the blending results exceed the company's specifications. Regarding tonnage, the company uses only a small amount of ROM, so it cannot fully maximize ROM with low-grade material. The research aims to optimize ROM with Al2O3 levels below 46% that are not selling well, thereby maximizing both grade and tonnage. The study calculates the blending activities in a barge with a capacity of 9.500 tons. Blending uses a 3-ROM composition and is simulated in blending activities using the simplex method to achieve optimal tonnage, in line with customer-grade requirements. The blending calculation results for bauxite using the simplex method show ROM 03 at 3.790,84133 tons, ROM 06 at 3.451,05238 tons, and ROM 12 at 2.248,10629 tons, with Al2O3 at 46,171%, SiO2 at 12%, and RSiO2 at 4%.